(3GdGbJQGM aj CUhd GdfMh hLOdgs - (3YHO GdQMef Hf CHj HcQ Hf eMeO GdNVjQj GdSjhWj, CHh GdaVd , LdGd GdOjf , J (B911 (3g`s ((3CMeO GdCMeOi GdbGOQi GdQaGYi GdSYOi GdYjOQhSi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CQTOfG dEHJcGQ gPG GdfeW hHYO agPG cJGH ZQjH GdhVY YLjH GdUfY ai Yde de CSHb Edi JQJjHg hde CJbOe Edi JgPjHg hgh CUhd GdfMh s
(3BNQgG (B:s
(3bGd ai GdNUGFU EPG ChGc GdbjGS Edi TF eG Je SeYJ GdYQH bO fWbJ ajg jTF BNQ Ydi bjGS ZjQg aOY eG cfJ Ydjg Edi eG fU Ydjg GfJgi Je gPG GdcJGH s
(3HgG fXGe GdJYbjHIs
(3cJHJ ChGFd GdabQGJ HeOGO CMeQs
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B301 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B535s
Keywords: (3GdfMhs